IMPLEMENTASI KURIKULUM MERDEKA MELALUI METODE BELAJAR MONTESSORI PADA PENDIDIKAN ANAK USIA DINI (PAUD) PERCONTOHAN PLAMBOYAN 3 KARAWANG - Syaharani, Nur Aisyah; Dewi, Ratnasari; Pujiarto, Pujiarto (Comm-Edu (Community Education Journal), 2025)
Early childhood education must be implemented using the right approach, in order to support the cognitive, affective and psychomotor abilities of students. Therefore, a curriculum and learning methods are needed that must be relevant to interconnected science. This study aims to describe the implementation, supporting and inhibiting factors, and the results of the application of the independent curriculum through the Montessori learning method at PAUD Perpilot Plamboyan 3 Karawang. The independent curriculum emphasizes learning activities using the concept of "Freedom to Learn, Freedom to Play". This is in line with the Montessori learning method which emphasizes the freedom of children to be able to explore according to the needs and interests of each child through the involvement of all five senses. The method used in this study is a qualitative descriptive method, namely a research method that focuses on analyzing and reconstructing according to the data obtained. Data collection techniques use observation, interviews and documentation. While the subjects of this study were one principal, two educators and three parents of students. The results of the study showed that the implementation of the independent curriculum through the Montessori learning method at PAUD Percontohan Plamboyan 3 Karawang has been running well in accordance with the independent curriculum reference by combining Montessori principles in learning activities. Where students are focused on 3 main focuses of learning, namely intracurricular, co-curricular and extracurricular.